Dinamika Pesantren Nahdlatul Wathan dalam Perspektif Pendidikan, Sosial, dan Modal - Nahdi, Khirjan (Program Pascasarjana UIN Sunan Ampel Surabaya, 2013)
This article speaks of the dynamics of the Nahdlatul Wathan Pesantren by analyzing its spiritual, social and cultural capitals. The complex nature of the relationship between one capital and another and how this relationship has become the source of the physical and academic development, is in itself an interesting issue to explore. But the Pesantren is not only the product of this relationship. It is also the product of the system that its leaders have built. The paper tries to analyze these dynamics and the changes it has gone through by employing the social, capital and educational theories. To arrive at the objective conclusion, the paper treats the Pesantren as a social system in which triadic relationship between structure, ideology, and culture is found. As a social system, the Pesantren has also to consider the external forces which it is certainly part of. But it is exactly here that the Pesantrenâand any social system in that matterâwill find itself in a serious dilemma. How the Pesantren will deal with the external forces will be also the issue that the paper is interested to discuss, albeit briefly.